Behavioral, physiological, and blood biochemistry of Friesian Holstein dairy cattle at different altitudes in West Java, Indonesia (Biodiversitas Journal of Biological Diversity, 2022)
Abstract. Tanuwiria UH, Susilawati I, Tasrifin DS, Salman LB, Mushawwir A. 2021. Behavioral, physiological, and blood biochemistry of Friesian Holstein dairy cattle at different altitudes in West Java, Indonesia. Biodiversitas 23: 533-539. For dairy cows, the study of physiological aspects and those related to it is very important based on altitude. The data of this study are the main considerations to determine the ability of homeostasis, prediction of production and appropriate feed management. This study aims to examine the behavior, physiological abilities, and blood plasma biochemistry of sixty dairy cows. It was conducted using three locations in West Java Province based on topography, namely: (i) location with topography 350-500 meters above sea level (masl): Sukabumi Regency; (ii) location with topography 550-750 masl: Sumedang Regency; and (iii) locations with topography > 800 masl: Bandung Regency. Furthermore, 5 mL of blood samples were taken accurately, using a syringe and a 5 mL tube containing EDTA, respectively. Blood sampling was taken carefully from the jugular vein of dairy cows at the beginning of every month for six sampling periods. After each collection, the whole blood was separated from the plasma directly using a centrifuge, with a speed of 4500 ppm for 7 minutes. The plasma obtained was used to measure the value of blood biochemistry related. The plasma analysis was conducted using a Kenza 240TX model spectrophotometer. The procedure for analyzing blood samples followed the instructions listed in the randox and biolabo kits. Furthermore, behavioral and thermoregulation measurements were performed every week during this research. The results showed an increase in dairy cows' time spent lying and drinking at low altitudes compared to dairy cows at high altitudes. In contrast, rumination and feeding activities were decreased, as shown in the blood's physiological response and biochemical profile. Dairy cows appear to be more challenging to adjust physiologically at lower altitudes.